Upcycling: Cara Kreatif Remaja Menyelamatkan Lingkungan dan Meningkatkan Ekonomi - Nanda Qurrata A’yuni; Nur Dwi Andhika Putra; Sultan Kayyis Giandra; Yuliana Yuli; Mulyadi Mulyadi; Suhaidi Suhaidi (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
The issue of plastic waste in Indonesia has reached a critical level, with an annual production of 64 million tons. To address this challenge, an educational approach that integrates practical and meaningful aspects, especially for the younger generation, is necessary. This study implements Project-Based Learning (PjBL) with an upcycling approach to enhance students' environmental awareness, creativity, and entrepreneurial spirit. The methods used include socialization and hands-on practice, where students are encouraged to create economically valuable products from plastic and paper waste. This activity involved 36 teenagers divided into groups to produce upcycled products such as plant pots and pencil holders. The results of this project indicate an increase in students' awareness and skills in waste management, as well as the creation of upcycled products with market value. This study further confirms that project-based learning can positively impact environmental and entrepreneurial education in schools, aligning with the goal of nurturing a generation that is both environmentally conscious and economically self-sufficient.